FIELD-BASED EXCURSION (FBE) IN THE TEACHING AND LEARNING OF GEOGRAPHY IN SOME SELECTED SECONDARY SCHOOLS IN ONDO STATE, NIGERIA - Olabode, Abiodun Daniel (Journal of Geography Science and Education, 2023)
The age long tradition of Field-Based Excursion (FBE) is being eroded as effective learning strategy in secondary schools. This study considers investigating FBE and the teaching and learning of geography in some selected secondary schools in Akoko Southwest, Ondo State, Nigeria with a view to examining; the practice of FBE in the selected secondary schools,  students’ perceptions to FBE practice in secondary school, FBE and perceived relationship with geography subject, and FBE and learning impacts on secondary school students. The sample population consists of students of secondary school offering Geography as a subject in Akoko Southwest Area of Ondo State, Nigeria. Purposive sampling technique was adopted in selecting twelve (12) secondary schools, while ten (10) students each were randomly selected from sampled schools. This sample gave a total of one hundred and twenty (120) respondents in this study. Learning and Excursion Questionnaire (LEQ) was built using four points Likert scale with Mean Weight Values (MWV) and Grand Mean Value (GMV) for perception analysis. The decision states, accept the perception if the MWV is greater than the MWV; and reject, if otherwise. Results show that; responses denote excursion is no longer part of school curriculum, group excursion could be a preferred mode of FBE for optimum productivity, all aspects of  geography require FBE for better understanding” was ranked 1st on MWV=3.55, which signifies high level of relationship,  It is worthy of note that significant impacts of FBE has far enriching impacts on students’ learning habits.  The study concludes that efforts are needed to reintroduce FBE for quality educational delivery. It therefore recommends that there should be a reintroduction of FBE into secondary school curriculum so it can be made compulsory for students. Government and stakeholder at different levels should ensure adequate sponsor of FBE to bridge the cap for less privileged students. Teachers should introduce field-based approach to teaching methods.